L’autonomie de l’élève et ses supports pédagogiques - Héloïse Durler (Recherches en Éducation)
This contribution is based on an ethnographic study on teaching practices regarding primary school student autonomy. It highlights the tools used in observed classes and the intellectual prerequisite abilities of students. It deals with the plurality of these tools used by the students, in particular those considered "deviant" by teachers. Deviance categories are analyzed as indications of prerequired skills existence. They contribute to the formation of social inequalities in the first years of schooling because they are not explicitly objectified and taught.